Sjögren's syndrome: a stepwise approach to the use of diagnostic tests. Issue 5 (May 1992) - Coll, J; Porta, M; Rubiés-Prat, J; Gutiérrez-Cebollada, J; Tomás, S
Abstract : One hundred and forty two patients (62 with definite Sjögren's syndrome, 24 with probable Sjögren's syndrome, and 56 in whom Sjögren's syndrome was finally ruled out) were studied. Schirmer's test and rose bengal staining for the diagnosis of keratoconjunctivitis sicca and salivary scintigraphy and a labial biopsy sample for the diagnosis of xerostomaia were studied in all patients. Rose bengal staining showed high specificity (98%) but low sensitivity (55%). All patients with positive rose bengal staining results had associated xerostomia. In the rose bengal staining positive patients, scintigraphy had 100% specificity. A labial biopsy sample showed high sensitivity in the rose bengal staining, salivary scintigraphy positive group, and high specificity in the rose bengal staining positive, salivary scintigraphy negative group. In patients with negative rose bengal staining, salivary scintigraphy showed 96% specificity and 36% sensitivity. A labial biopsy sample had a sensitivity and specificity greater than 90% in rose bengal staining negative patients. Only 29 biopsy samples were needed to achieve a diagnosis of Sjögren's syndrome in 142 patients (20%). Hence the suggested approach may make it unnecessary to take biopsy samples in approximately 80% of patients with suspected Sjögren's syndrome. Using the stepwise approach of first rose bengal staining, then salivary scintigraphy, and eventually a labial biopsy sample in patients with suspected Sjögren's syndrome, the diagnosis is relatively simple.